Synthesis and Characterization of New Selenonitrone Derivative and Its Effect on Breast Cancer Cell Line Viability in Vitro (Baghdad Science Journal, 2019)
New nitrone and selenonitrone compounds were synthesized. The condensation method between N-(2-hydroxyethyl) hydroxylamine and substituted carbonyl compounds such as [benzil, 4, 4́-dichlorobenzil and 2,2́ -dinitrobenzil] afforded a variety of new nitrone compounds while the condensation between N-benzylhydroxylamine and substituted selenocarbonyl compounds such as [di(4-fluorobenzoyl) diselenide and (4-chlorobenzoyl selenonitrile] obtained selenonitrone compounds. The condensation of N-4-chlorophenylhydroxylamine with dibenzoyl diselenide obtained another type of selenonitrone compounds. The structures of the synthesized compounds were assigned based on spectroscopic data (FT-IR, 1H-NMR, 13C-NMR, MS and elemental analysis. The result spectra and the result of elemental analysis were verified the expected structure. The results of new selenonitron derivative (N1) effect on the MDA-MB-231 breast cancer cells in vitro revealed that is an increase in the proliferation of cells with increased concentrations of selenonitron at all periods of the times.